UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPA MELALUI MODEL PEMBELAJARAN PROBLEM POSING PADA SISWA KELAS III SDN 45 PULAU KARAM - Yarmaneli, Yarmaneli (Jurnal Manajemen Pendidikan, 2018)
Based on the learning outcomes of Class III students at SDN 45 Pulau Karam in science subjects it was found that student learning outcomes in science subjects were still very low. The average student learning outcomes are still under the KKM. The purpose of this study is to describe and obtain information about the Efforts to Improve student learning outcomes in science subjects through Problem Posing Learning Model in Class III SDN 45 Karam Island. This research is a classroom action research. The procedure of research in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 20 Class III students at SDN 45 Karam Island. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of the research and discussion that have been put forward, it can be concluded that the Problem Posing Learning Model can improve student learning outcomes in science subjects at SDN 45 Karam Island. Student learning outcomes from cycle I to cycle II. The learning outcomes of students in the first cycle were 57.75 (sufficient) increasing to 84.75 (good) with an increase of 27%.